MODEL HARMONISASI HUKUM PIDANA DAN PERDATA UNTUK PENYELESAIAN KASUS KEKERASAN - HASNIA, HASNIA; MUNAWWARAH, SITTI; SARJONO, ANASTASIA; UMAR, NURIFANA (GANEC SWARA, 2024)
Violent crimes often involve two legal aspects, namely criminal and civil, which require harmonization to ensure substantive justice for victims and perpetrators. The main problem faced is the separation of criminal and civil legal processes, which often hinders the holistic restoration of victims' rights. This study aims to analyze the harmonization mechanism of criminal and civil laws applied in various countries, including the United Arab Emirates, Canada, Germany, and Indonesia, and to develop a legal harmonization model that is appropriate to the Indonesian context by considering local values and international standards. The research method used is normative with a statutory regulatory approach, conceptualization, comparison, and history, which focuses on the analysis of relevant legal regulations and legal theories. The results of the study indicate that legal harmonization can be achieved through integrated application, restorative justice mechanisms, and recognition of customary legal practices that do not conflict with human rights. A model that calls for the importance of national legal reform, integration of local values, and application of international standards to create a more responsive legal system. The main recommendations are strengthening legal infrastructure, training law enforcement officers, and implementing best practices from other countries.